The Effect of Social Skills Training on the Development of Social Skills among Preschool Children in Shahroud City, Iran, 2017 - Atena Rezaei; Golbahar Akhoundzadeh; Hamid Hojjati (Vesnu Publications, 2018)
Introduction: Development of social skills is one of the achievements of childhood that predicts students' social behaviors, future academic achievement, and future career prospects. This study was conducted to evaluate the effect of social skills training on social skills development in preschool children in Shahroud City, Iran in 2017. Materials and Methods: This experimental study was conducted on 60 preschool children in two groups of experimental and control. In the experimental group, twelve 60-90-minute sessions of social skills training were performed in groups of 7-8 students. Data gathering tool was Matson social skills questionnaire, which data were collected via self-report by parents and educators. Data were analyzed using descriptive statistics (tables, mean, and standard deviation), and inferential tests (paired t, independent t, and ANCOVA tests). Results: Before the intervention, there was not any significant difference in social skills between the groups from educators' and parents' points of view. However, after the intervention, there was significant differences between the groups from educators' (P = 0.04) and parents (P = 0.02) points of view, and social skills was significantly better among experimental group. Conclusion: Considering the effectiveness of social skills training, it can be said that improving and developing social skills at preschool age can be the basis for children's future educational, occupational, and behavioral achievements. Therefore, given the importance of educational opportunities at early childhood, health officials and health professionals need to pay more attention to this issue.